A Prototype of Obstacle Avoidance for Autonomous Vehicle - Khan, Burhan; Nizamani, Sehrish; Kazi, Nabeel Hussain; Nizamani, Saad; Nizamani, Sarwat (Iraqi Journal of Science, 2022)
Obstacle avoidance is one of the major tasks needed to be carefully focused by the autonomous system designers. In this digital era, most industries are moving towards autonomous systems. Obstacle avoidance is considered as a primary concern for any autonomous system. In this paper, a prototype of an autonomous vehicle is presented, which is capable of obstacle avoidance using an ultrasonic sensor for its movement and avoidance. An Arduino microcontroller is used to achieve the desired operation. In order to achieve the desired task of the proposed system, a proper methodology is followed which combines appropriate selection of hardware components as well as logic design of actions for obstacle avoidance. The proposed system can easily detect an obstacle, and move accordingly towards the safe path, by first detecting and then verifying the safe path. This can be very useful if implemented in real life.  It can ultimately reduce the chances of accidents of trains and road vehicles which will save lots of lives.  It can also detect broken roads and train tracks, which may result in reducing the chances of accidents to some extent. The accuracy of the autonomous vehicle depends on the output received by the ultrasonic sensor; therefore, it is not affected by the lighting environment. The prototype has been tested in various experimental settings and achieves appropriate results.